Multiple Episodes of Catastrophic Flooding in the Peshawar Basin During the Past 700,000 Years - Burbank, Dotjglas W. (Journal of Himalayan Earth Sciences, 1983)
At least 40 catastrophic floods inundated the Peshawar Basin in prehistoric times. A sequence of graded beds up to 25m thick near Paran record these flood events. These older floods resulted from significantly high flows than those of the well-documented floods of 1800’s. Such floods can be a real threat to the safety of Tarbela Dam and a careful monitoring of the Indus and its major tributaries is required and suggested.